LANGSTON HUGHES AND HIS POETRY - Sultanbayeva Iroda Bustanbeks girl (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
ABSTRACT: James Mercer Langston Hughes is an American poet, public figure, author, playwright, and columnist from Joplin, Missouri. One of the innovators of the literarary movement called jazz poetry, Hughes is known as a leader of the Harlem Renaissance. In this article, I will provide information about Langston Hughes, the central figure of the flourishing of black intellectual, literary and artistic life that took place in several American cities in the 1920s, especially in Harlem, and his creative works. While getting acquainted with the works of English poets, the beautiful works and meaningful poems of Langston Hughes atrracted my special attention.